PENYULUHAN KEUANGAN MIKRO DAN MANAJEMEN USAHA KECIL UNTUK ANGGOTA PKK DAN KADER POSYANDU DI DESA KARYAMEKAR, PASIRWANGI, GARUT, JAWA BARAT - Ayi Nurbaeti; Kus Indiyah; Gunanto Wardjono; Tri Yuni Susilowati; Wenny Djuarni (JURNAL ABDIMAS PLJ, 2025)
Empowering women through improving financial literacy and small business management skills is a crucial strategy for supporting the economic resilience of families and rural communities. This outreach program was conducted to provide understanding of the basic concepts of microfinance, household financial planning, and small-scale business management for Family Welfare Movement (PKK) members and Posyandu (Integrated Service Post) cadres in Karyamekar Village, Pasirwangi District, Garut Regency, West Java. The implementation method included interactive outreach, group discussions, budgeting simulations, and simple mentoring on financial record-keeping. Participants were actively involved in identifying the challenges they face in financial management and micro-enterprises and formulating strategies that can be implemented according to the socio-economic conditions in their communities. The results of the activity demonstrated an increased understanding of the importance of financial record-keeping, household budgeting, capital management, and simple marketing strategies for small businesses. Participants also began to be able to apply basic steps in managing home businesses in a more structured and effective manner, particularly in the aspects of business planning and evaluation. This activity is expected to be the first step in strengthening the economic capacity of women in Karyamekar Village. Further recommendations include the need for ongoing mentoring, further training in digital marketing, and the formation of joint business groups to ensure the program's sustainability and provide broader economic benefits to the village community.